2019
DOI: 10.3390/cancers11121924
|View full text |Cite
|
Sign up to set email alerts
|

Gathering Novel Circulating Exosomal microRNA in Osteosarcoma Cell Lines and Possible Implications for the Disease

Abstract: One of the goals of personalized medicine is to understand and treat diseases with greater precision through the molecular profile of the patient. This profiling is becoming a powerful tool for the discovery of novel biomarkers that can guide physicians in assessing, in advance, the disease stage, and monitoring disease progression. Circulating miRNAs and exosomal miRNAs, a group of small non-coding RNAs, are considered the gold standard diagnostic biomarkers for human diseases. We have previously demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…A recent study by Wang et al reported that exosomal miR-21 expression in serum and plasma from patients with OS differed from that in normal patients, and that exosomal miR-21 plays important roles in OS tumorigenesis [34]. In addition, a review by Cuscino et al revealed that eight exosomal miRNAs may be implicated in OS progression [35].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wang et al reported that exosomal miR-21 expression in serum and plasma from patients with OS differed from that in normal patients, and that exosomal miR-21 plays important roles in OS tumorigenesis [34]. In addition, a review by Cuscino et al revealed that eight exosomal miRNAs may be implicated in OS progression [35].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that serum exosome derived miR-675 expression may serve as a new biomarker for osteosarcoma metastasis ( Gong et al, 2018 ). Cuscino et al identified eight novel miRNAs in osteosarcoma cell lines and their release in exosomes, which demonstrated that these candidate miRNAs could potentially represent biomarkers for osteosarcoma ( Cuscino et al, 2019 ). Yoshida et al reported that the levels of exosomal miR-25-3p were significantly correlated with a poor prognosis of osteosarcoma ( Yoshida et al, 2018 ).…”
Section: Potential Application Of Exosomes In Osteosarcomamentioning
confidence: 99%
“…Many studies on the use of circulating microRNAs as biomarkers in the diagnosis of OS have been carried out and published. They concluded that several microRNAs were found to be differentially expressed-either up-or downregulated [4,9]. Despite the useful number of publications on this subject, there are some inconsistencies between them, due to differences in the detection methods, the analysis of microRNAs expression, etc.…”
Section: Introductionmentioning
confidence: 99%